A highly active and stable hybrid oxygen electrode for reversible solid oxide cells. (22nd October 2021) - Zhao, Zhe; Qi, Huiying; Tang, Shuai; Zhang, Chao; Wang, Xiuling; Cheng, Mojie; Shao, Zhigang
Abstract: Reversible solid oxide cells (RSOCs) have attracted increasing attention due to the potential realizing the deep coupling between hydrogen and electricity. An efficient and stable oxygen electrode is needed for developing RSOCs. Herein, we report a nanostructured hybrid with a nominal composition of BaZr0.2 Co0.8 O3-δ as oxygen electrode. The chemical composition, crystal structure and physicochemical properties of the BaZr0.2 Co0.8 O3-δ hybrid have been characterized. The results show that the sintered BaCo0.8 Zr0.2 O3-δ has grown into a hybrid, consisting of cubic perovskite BaZr0.82 Co0.18 O3-δ, hexagonal perovskite BaCo0.96 Zr0.04 O2.6+δ and a small quantity of hexagonal perovskite BaCoO3 . The cell with BaZr0.2 Co0.8 O3-δ hybrid oxygen electrode delivers a current density of 2.09 A cm −2 @0.7 V in SOFC mode, and gives −1.43 A cm −2 @1.3 V in SOEC mode for steam electrolysis. The BaCo0.8 Zr0.2 O3-δ cell shows a smooth transition from SOEC to SOFC, and gives no obvious degradation after 100 times SOEC↔SOFC cycle operation. Highlights: A nanostructured hybrid oxygen electrode is developed for reversible solid oxide cells. The hybrid oxygen electrode shows excellent performance for both ORR and OER. The cell delivers a current density of 2.09 A cm −2 @0.7 V in SOFC mode, and gives −1.43 A cm −2 @1.3 V in SOEC mode. The hybrid oxygen electrode gives no obvious degradation after 100 times SOEC↔SOFC cycle operation.